Method to obtain platelet-rich plasma from rabbits (Oryctolagus cuniculus) - Pazzini, Josiane M. [UNESP] (2016)
Platelet-rich plasma (PRP) is a product easy and inxpesnsive, and stands out to for its growth factors in tissue repair. To obtain PRP, centrifugation of whole blood is made with specific time and gravitational forces. Thus, the present work aimed to study a method of double centrifugation to obtain PRP in order to evaluate the effective increase of platelet concentration in the final product, the preparation of PRP gel, and to optimize preparation time of the final sample. Fifteen female White New Zealand rabbits underwent blood sampling for the preparation of PRP. Samples were separated in two sterile tubes containing sodium citrate. Tubes were submitted to the double centrifugation protocol, with lid closed and 1600 revolutions per minute (rpm) for 10 minutes, resulting in the separation of red blood cells, plasma with platelets and leucocytes. After were opened and plasma was pipetted and transferred into another sterile tube. Plasma was centrifuged again at 2000rpm for 10 minutes; as a result it was split into two parts: on the top, consisting of platelet-poor plasma (PPP) and at the bottom of the platelet button. Part of the PPP was discarded so that only 1ml remained in the tube along with the platelet button. This material was gently agitated to promote platelets resuspension and activated when added 0.3ml of calcium gluconate, resulting in PRP gel. Double centrifugation protocol was able to make platelet concentration 3 times higher in relation to the initial blood sample. The volume of calcium gluconate used for platelet activation was 0.3ml, and was sufficient to coagulate the sample. Coagulation time ranged from 8 to 20 minutes, with an average of 17.6 minutes. Therefore, time of blood centrifugation until to obtain PRP gel took only 40 minutes. It was concluded that PRP was successfully obtained by double centrifugation protocol, which is able to increase the platelet concentration in the sample compared with whole blood, allowing its use in surgical procedures. Furthermore, the preparation time is appropriate to obtain PRP in just 40 minutes, and calcium gluconate is able to promote the activation of platelets.